ABO blood group and the risk of aortic disease: a nationwide cohort study. Issue 10 (1st October 2020) - Zindovic, Igor; Edgren, Gustaf; Nozohoor, Shahab; Majeed, Ammar
Abstract : Objectives: To analyse the association between ABO blood group and aortic disease using data on blood donors and transfused patients from Sweden. Design: This was a retrospective study using data from the Swedish portion of the Scandinavian Donations and Transfusions Database. The association between ABO blood group and aortic disease was analysed using log-linear Poisson regression models and presented as incidence rate ratios (IRRs). Setting: Swedish population-based study. Participants: The study cohort consisted of 1 164 561 Swedish blood donors and 961 637 transfused patients with a combined follow-up time of 29 390 649 person-years. Primary and secondary outcome measures: IRRs of aortic events (ie, aortic aneurysms and/or aortic dissections) in relation to patient blood group. Results: A total of 20 684 aortic events occurred during the study period. Non-O donors and patients had similar incidence of aortic events when compared with blood group O donors and patients with an IRR of 0.98 (95% CI, 0.93–1.04) and 1.00 (95% CI, 0.97–1.03), respectively. There were no differences between non-O and blood group O individuals when aortic dissections and aortic aneurysms were analysed separately. Blood group B conferred a lower risk of aortic aneurysms in the patient cohort when compared with blood group O (IRR, 0.90; 95% CI, 0.85–0.96). Conclusions: In the present study, there were no statistically significant associations between ABO blood group and the risk of aortic disease. A possible protective effect of blood group B was observed in the patient cohort but this finding requires further investigation.